Results Of The Research On The Basis Of The Parameters Of The Working Body Forming The Irrigation Equipment Of The Combined Aggregate - Khudoyarov, A.N.; Abdullaev, D.A.; Yuldasheva, M.A.; Khudoynazarov, D.O.; Kholdarov, M.; Nazirjonov, I. (International Journal of Psychosocial Rehabilitation, 2020)
Special attention is paid to the planting of ornamental trees and rare flower seedlings and medicinal plants in forestry plantations in the country. As no special aggregates have been developed to prepare the land for planting, the use of existing aggregates or their adapted variants leads to an increase in energy consumption and operating costs. Research methods and materials. The analysis and research developed a combined aggregate structure that performs the technological processes of preparing forest plantations for planting in one pass of the unit, and used theoretical mechanics, higher mathematics and mathematical statistics to theoretically substantiate the size of its working body. Research results. When comparing the existing and proposed technologies, the proposed technology significantly reduces the consumption of labor, energy and fuels due to the lack of tillage, mulching and plowing, a sharp reduction in the number of field trips (5-6 times to 3 times). was found not to condense. Theoretical studies have identified the main parameters for the working body, which forms the combined aggregate irrigation canals, to produce the required level of irrigation canals and piles with low energy consumption. Conclusion. Depth of soil to a pan, which impedes rooting, should be 7–8 cm. The height of the opening chest is at least 20.5 cm, the opening angle of the wings is in the range of 60–65,, the angle of entry into the soil is 35–40º, the angle of the side clipping is 35–38º, the width of the wings and the length of the body should be at least 41 cm and 78 cm, respectively.